Determinantes de la inversión pública en el Perú para el periodo 1980-2017 - Rodríguez Díaz, Richard Wiener (2019)
The main objective of this research work is to analyze the determinants that affect public investment in Peru for the period 1980-2017. For the elaboration of this investigation, annual data of the variables Public Investment, Gross Domestic Product, Tax Income and Fiscal Deficit were used; these being the quantitative variables, while the qualitative variable used in the econometric model through dummy variables is the presence of a tax collection entity with autonomy in its policies, this being the Superintendence of Customs and Tax Administration, incorporating it into the econometric model by dichotomy, being 0, the absence of the National Superintendence of Customs and Tax Administration (SUNAT) and being 1, the presence of SUNAT as a tax collector; Corruption is also an important qualitative variable that affects the amount of public investment. The data used in this investigation were collected from the Central Reserve Bank of Peru (BCRP), the National Superintendence of Customs and Tax Administration (SUNAT) and the National Institute of Statistics and Informatics (INEI). The information was used and the following equation is posed: IP = 0.720034 PBI-0.035372 DF + 0.027874IT + 0.032889PS + ut The results of the investigation show that the significant quantitative variable is the real GDP, tax revenues; Regarding the qualitative variable, it shows that it is significant to the amount of public investment in Peru in the period 1980-2017. Therefore, it is concluded that the determinants of Public Investment is the Gross Domestic Product, Tax Income and the presence of a tax collection entity with autonomy in its policies, being the Superintendence of Customs and Tax Administration.